Association between left ventricular remodeling and coronary chronic total occlusion in hypertensive coronary artery disease patients - Wujian He; Qiang Yao; Duanbin Li; Xiangqian Sui; Wenbin Zhang (Scientific Reports)
Abstract Hypertensive left ventricular (LV) remodeling may influence coronary artery pathology due to anatomical proximity, yet its association with coronary chronic total occlusion (CTO) remains unclear. This cross-sectional, hypothesis-generating study included patients with coexisting coronary artery disease (CAD) and hypertension. LV geometry was classified by echocardiography as normal, concentric remodeling (CR), concentric hypertrophy (CH), or eccentric hypertrophy (EH). CTO was identified by coronary angiography. Logistic regression models were used to evaluate the association between LV geometry and CTO incidence. A total of 3430 patients were included, with a mean age of 65.3 years and 68.9% male. LV remodeling was present in 2427 (70.8%) patients. CTO lesions were identified in 300 (8.7%) patients, with incidence rates of 6.1% in normal geometry, 6.9% in CR, 9.9% in CH, and 12.7% in EH. Compared to normal geometry, LV remodeling was associated with a higher risk of CTO (OR, 1.696; 95% CI 1.258–2.285, p = 0.001), particularly in patients with CH (OR, 1.798; 95% CI 1.276–2.535, p = 0.001) and EH (OR, 2.355; 95% CI 1.656–3.349, p < 0.001). These observational findings suggest an association between LV remodeling and CTO in hypertensive CAD patients, although causal inference remains limited and further prospective investigations are warranted.